English Teachers’ Perceptions of the Adoption of Culturally-Responsive Pedagogy (CRP) in Multicultural Classrooms - Lia Haryana; Utami Widiati (Universitas Bengkulu, 2025)
Culturally Responsive Pedagogy (CRP) in developed countries, little research reports the studies of teachers’ perceptions of CRP in the context of developing countries, like Indonesia. To fill this empirical gap, the present study investigated English teachers’ perceptions of the adoption of CRP in the Indonesian context in terms of four dimensions of CRP, namely: teachers’ ethic of care, teachers’ cultural values, teachers’ pedagogical expertise, and teachers’ supportive behavior. Four professional English teachers from a culturally diverse school were recruited as participants in this current study. Elicited using semi-structured interviews, the collected data were analyzed qualitatively. Findings reveal that the participants perceive the adoption of CRP positively. These positive perceptions indicate that the teachers hold positive views on CRP, which means they perceive that CRP is essential to be adopted in the teaching and learning process, especially for teaching culturally diverse students. The results of this study can inspire other teachers who teach diverse students and who are interested in multicultural education to adopt the concept of CRP in their teaching. This study also ends with suggestions for policymakers, like the Institute for Quality Assurance and learning development (LPMPP), to provide training, workshops, seminars, and other activities that relate to the concept of CRP. Besides, it is recommended for future researchers to investigate further the concept of CRP by using different research subjects and different research methods. Keywords: Culturally Responsive Pedagogy (CRP); diversity, learning environment, multicultural education